2021
DOI: 10.35857/2663-3566.121.13
|View full text |Cite
|
Sign up to set email alerts
|

Creation of electrically conductive composite ceramics based on facing tiles with the addition of SiC

Abstract: In the article, the creation of electrically conductive composite ceramics based on facing tiles with the addition of SiC with specified electrodynamics’ characteristics was considered. To obtain a press powder, the raw materials in a predetermined amount were weighed, 10, 20 and 30 % silicon carbide were added and subjected to wet grinding in a ball mill. The resulting slip was dried in a drying oven and passed through a № 05 sieve. The finished press powder for facing ceramics with SiC, moistened to 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…1, d) has the lowest open porosity. This is also confirmed by a previous study [16], which indicated its characteristics: open porosity -12.51 %, water absorption -5.88 %, apparent density -2.13 g/cm 2 , resistivity -0.43•10 6 Ω•m.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1, d) has the lowest open porosity. This is also confirmed by a previous study [16], which indicated its characteristics: open porosity -12.51 %, water absorption -5.88 %, apparent density -2.13 g/cm 2 , resistivity -0.43•10 6 Ω•m.…”
Section: Resultssupporting
confidence: 90%
“…The obtained raw material was dried in a drying cabinet. The finished semi-finished product was fired in a silite furnace at a firing temperature of 1120-1140 °C, with exposure at the maximum temperature for 5-10 min [16]. The mass composition of raw materials for the production of electrically conductive composite ceramics from SiC is presented in the Table 1.…”
Section: Methodsmentioning
confidence: 99%